PENENTUAN PRIORITAS LOKASI PENGEMBANGAN SISTEM ANGKUTAN UMUM PERDESAAN DI JAWA TENGAH DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Christnawati, Priscilla Tiara; Wangi, Intan Puspa; Basuki, Kami Hari; Indriastuti, Amelia Kusuma (Jurnal Karya Teknik Sipil, 2016)
Optimalization of rural public transit is needed to improve people’s prosperity, especially for those who live in remote rural area. Rural public infrastructure nowadays hasn’t been optimized properly by the government yet, proven by a few number of region which already has urged rural transportation infrastructure. This research aims to select the location of rural public transit system development in Central Java according to priorities. This research focuses on the region which has had the interregion rural public transit system route already. The analysis of developing system of rural public transit defines the location priority by Analytical Hierarchy Process (AHP) method and recommends its road typical. To determine location priority uses Analytical Hierarchy Process (AHP) method. Determination of criteria based on the results of questionnaires distributed to the expert. The criteria are total area, the number of demand, population density, LQ index of rural public transit availability, the number of trip distribution, primary-food volume, the number of rural public transportation supply, and the number of vehicles-owner. Utility assessment is done by using secondary data. From these two steps, location priority will be determined. The last step is identified whether it is necessary or not to advance its road typical based on the Region Land Use Planning as mentioned in the valid regulation. The result shows that the most significant factor in determining the rural public transit system development is the number of demand which gets 25,7%. The result clearly shows that Brebes and Tegal has been admitted as the most priority region of rural public transit system development. Amongst of all the routes of interregion rural public transit, there are two routes which should be advanced its typical road: Boyolali-Sragen route and Sukoharjo-Boyolali route. The conclusion of this research is there is still a few of region on Central Java which already has the interregion rural public transit system route –only nine regions. The government should support another region to supply this route access.